A reference data model to support biomass supply chain modelling and optimisation. (September 2016) - De Meyer, Annelies; Snoeck, Monique; Cattrysse, Dirk; Van Orshoven, Jos
Abstract: This paper presents a generic and flexible reference data model meant as the blueprint of the database component of information and decision support systems related to different types of biomass-based supply chains (e.g. first to fourth generation biomass for production of bioenergy and biomaterials). The data model covers the biomass types and handling operations as characterised by their attributes and mutual relationships resulting from a life cycle inventory analysis. The data model enables the identification of the possible operation sequences in the specified chain. This functionality is demonstrated in a case study in which biomass from tall herb communities and mesotrophic grasslands is supplied for biogas or compost production. A comparative analysis has pointed out that the data model includes the required object types to add specific attributes of biomass supply chain simulation and optimisation models (such as spatial and temporal dimensions). Highlights: LCA based high level process model for biomass-based supply chains. Blueprint of database component of information and decision support systems. Reference data model to enable exchange of models among users. Reference data model as a standard exchange format to benchmark different tools. Demonstration of the functionalities of the data model in a real world case study.